Analisis Pemanfaatan Potensi Lokal Sebagai Objek Wisata Untuk Meningkatkan Kesejahteraan Masyarakat Kaitannya Pada Pencapaian Sustainable Development Goals - Rifqi, Moch Rizfani; Kamilah, Kamilah; Syahriza, Rahmi (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
Currently, there are more poor people in Indonesia in rural areas compared to urban areas. In Pematang Johar village, the majority of people are farmers, livestock breeders, housewives or do not work. This tourist village was formed with the aim of helping the community's economy. Tourism villages are one of the tourism sectors that are expected to realize the goals of the Sustainable Development Goals. This research aims, firstly, at how to utilize local potential as a tourist village object to improve community welfare, secondly at how to utilize local potential as a tourist attraction in relation to achieving the Sustainable Development Goals program, thirdly at obstacles in developing tourist villages. The research approach used in this research is descriptive qualitative with data collection methods, namely using interview, observation and documentation techniques. The results of the research conclude that first, local potential, especially in tourist villages, is a new industrial sector that can improve the welfare of the community, the existence of tourist villages makes a big contribution to the community's economy, community income increases and it can be said that with the existence of this tourist village, the lives of the people become prosperous. Second, the existence of tourist villages has a positive impact on several Sustainable Development Goals points, namely healthy and prosperous life, quality education, gender equality, and decent work and economic growth, but poverty alleviation has not been completely resolved. The three obstacles that exist in developing tourist villages are that there is still a lot of infrastructure that must be built and in the development process, also providing awareness of tourism to the community is still an obstacle. Also, we still have to create quality human resources.